2018
DOI: 10.1063/1.5050250
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of secondary electron emission: A new route to nanoscale temperature measurement using scanning electron microscopy

Abstract: Scanning electron microscopy (SEM) is ubiquitous for imaging but is not generally regarded as a tool for thermal measurements. Here, the temperature dependence of secondary electron (SE) emission from a sample's surface is investigated. Spatially uniform SEM images and the net charge flowing through a sample were recorded at different temperatures to quantify the temperature dependence of SE emission and electron absorption. The measurements also demonstrated charge conservation during thermal cycling by placi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Comparing heating by the e-beam versus Joule heating of a PRT, the e-beam heating approach offers several advantages. First, although the e-beam based k -measurements in this study required additional microfabrication to create the PRT, in principle the temperature could instead be measured directly using the SEM , or TEM itself. This will greatly simplify the microfabrication and facilitate the e-beam heating and sensing at arbitrary locations and with various shapes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing heating by the e-beam versus Joule heating of a PRT, the e-beam heating approach offers several advantages. First, although the e-beam based k -measurements in this study required additional microfabrication to create the PRT, in principle the temperature could instead be measured directly using the SEM , or TEM itself. This will greatly simplify the microfabrication and facilitate the e-beam heating and sensing at arbitrary locations and with various shapes.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we have found the MEEHV by using a PRT to measure the temperature rise, which requires additional microfabrication and instrumentation, but in principle the temperature rise could instead be measured directly by SEM thermometry which is less accurate but simpler and noninvasive. 43 Note also that knowledge of G is not needed because it never enters into the calculation of the MEEHV (recall that the MEEHV was found in Figure 1b using arbitrary units on the E-axis). Knowledge of the MEEHV is also helpful for thermal metrologies which use the e-beam as a heater, because operating at the MEEHV gives the peak heating which maximizes the signal-to-noise ratio.…”
mentioning
confidence: 99%
“…Figure 1 shows a comparison between the simulated and experimental temperature dependencies of the total electron (TE = SE + backscattering electron [BSE]) yield, aiming to prove the reliability of the MC model. As a statement, although there is currently no temperature‐dependent experimental data reported on the Au element, Figure 1 adopts recent temperature‐dependent TE yield data for the silicon element measured by Khan et al [ 8 ] . It can be observed that the simulated curve is among the experimental data, indicating that an acceptable comparison has been achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Third, photoabsorption-induced heating or strain can also change the scattering processes in the sample and affect the net secondary electron yield. 37 For a monolayer of silicon nanoparticles, the absorbed laser power is less than 2.5% of the total incident power at 532 nm. The bulk aluminum-coated silicon substrate also provides good thermal conductance.…”
mentioning
confidence: 99%
“…The first two mechanisms (photon-impact-first electron-assisted and electron-impact-first photon-assisted) could be important in SUEM experiments but are unlikely to be relevant for the experimental conditions used here. Third, photoabsorption-induced heating or strain can also change the scattering processes in the sample and affect the net secondary electron yield . For a monolayer of silicon nanoparticles, the absorbed laser power is less than 2.5% of the total incident power at 532 nm.…”
mentioning
confidence: 99%